Contribution of work climate and leadership towards tutor performance in PKBM district in Pasaman district - Susiana, Aprina; Solfema, Solfema (Universitas Negeri Padang, 2025)
This study was motivated by the fact that some tutors were not yet able to make learning plans, implement learning, and evaluate learning. Most tutors tend to only provide notes without explaining the material given to students. This study aims to describe the contribution of the work climate of leadership and performance of PKBM tutors in Pasaman Regency, using a quantitative approach method with a population of 109 people from Package B tutors. This study used a random sampling technique because the area studied was quite large, namely Pasaman Regency, so 68 Package B tutors were selected as samples. The data collection technique used was a questionnaire and testing the research instrument using the Validity and Reliability Test. The data analysis technique for this study was the Descriptive Statistical Test, the Classical Assumption Test, and the Linearity Test. The results showed that the contribution of the work climate of PKBM tutors in Pasaman Regency obtained quite good results with an average total score of the work climate variable of 2.48, the work environment in PKBM was in the fairly good category, this shows that although the work atmosphere in PKBM was adequate, there were still several aspects that needed to be improved in order to support the tutor's performance optimally. The contribution of leadership to the performance of PKBM tutors in Pasaman Regency is in the fairly good category with an average total score of the leadership variable of 2.49, leadership in PKBM is considered capable of providing adequate influence but has not reached an optimal level. Based on the results of data collection, it can be concluded that the contribution of PKBM tutor performance is quite good, the results of the analysis show that the average total score of the performance variable reaches 2.49, which places the performance of tutors in PKBM in Pasaman Regency in the sufficient category, the score indicates that the tutors have carried out their duties adequately but there is still potential for improvement. Keywords: Work Climate, Leadership, Tutor Performance